HYPERLINKED LIBRARY : LIBRARY AS HUMAN - Safii, Moh; Dewi, Amalia Nurma (2018)
The purpose of this research to obtain a strategy from the Library of the State University of Malang is seen from the perspective of the Hyperlinked Library theory. Data is taken through interviews, observation, and documentation. Informants in this study were 2 library staff and researcher as participants. Selection of informants based on purposive sampling. This research used a qualitative method. Results of this hyperlinked library study at the Library of the State University of Malang based on the theory consisted of three namely Participatory Service (Web 2.0, Evaluation Meeting, Leadership Style, Open Minded), Transparency (Live Chat, Whatsapp, Discussion with lecturers of Library Sciences), Emerging Technology (creative and institutional support). Hyperlinked Library of Library of the State University of Malang can implemented until now because all staff has the enthusiasm that the patron is very important. The leadership of the organization facilitates every creative action of librarians who are encouraged to serve better. The organization is open to criticism and continues to evaluate.